The influence of organization citizenship behavior (OCB) and job satisfaction on performance employees of airnav indonesia at Juanda International Airport - Supardam, Fatmawati; Rahayu, Sri; Hardjanti, Wulandari; Yuliastanti, Rika; Supardam, Dhian (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to analyze the impact of Organization Citizenship Behaviour (OCB) and job satisfaction on employee performance at Juanda Airport. Using a field research method with a quantitative approach, this study involved 22 employees as samples taken from the Juanda Airport employee population. The results of data analysis using multiple linear regression analysis show that OCB and job satisfaction significantly contribute to improving employee performance. The results of these findings provide implications that management at Juanda Airport can strengthen organizational performance by encouraging participation in OCB and increasing employee job satisfaction. This research contributes to the understanding of the factors that influence employee performance in the work environment, especially in the context of services in the airport sector.